Soil conditions in the “donga” soils in subhumid zone in West Africa - AVAKOUDJO, JULIEN; KOUELO ALLADASSI, FÉLIX; KINDOMIHOU, Valentin; AKPLO, Tobi Moriaque; AGONVINON, Socrate; AMADJI, LUCIEN GUILLAUME; Sinsin, Brice A. (My University, 2021)
Abstract: Water erosion threatens large areas around the world. “Donga” is one of the witnesses of gully erosion in northern Benin, which induces serious threats to the natural habitats. This study was conducted to evaluate soil moisture content in different donga types (“microdongas”, “mesodongas”, and “megadongas”) and its variation at different topographic levels. The thermogravimetric soil moisture measurement technique was used for moisture estimation on saturated and unsaturated soil. Data were analyzed through analysis of variance test and t test with SAS software. The results showed that soil moisture content varied according to donga types. On unsaturated soil, higher difference (2.75%, p = 0.0328) was obtained in mesodongas at the middle followed by megadongas at the middle (2.6%, p = 0.034). On saturated soil, higher difference was obtained in mesodongas at the upstream (6.51%, p < 0.0001) at downslope (4.55%, p = 0.0032) and in the middle (4.32%, p = 0.0328) followed by microdongas at the upstream (2.25%, p < 0.0001). The findings in this paper should be useful to researchers looking for soil moisture information in subarid and subhumid zone at different topographic levels to develop afforestation strategies based on species that can make the best use of soil water.
Keywords: Key words: soil erosion; soil moisture; donga; topographic level; Benin